Benefit of Consumer Showrooming for a Physical Retailer: A Distribution Channel Perspective - Hao, Lin; Kumar, Subodha (Management Science, 2024)
Consumer showrooming has become a common phenomenon in the retail industry, but little is known about its influence on the interplay between an upstream supplier and a downstream retailer in a distribution channel. Our study examines such an influence by considering an upstream supplier who sells a product through a downstream physical retailer based on a wholesale contract. At the same time, based on an agency contract, the supplier sells the product on an online retail platform where a nonneglectable amount of consumer returns occurs due to product misfits. We find that, on the one hand, consumer showrooming enables the supplier to take a greater share of the offline channel profit by exploiting the physical retailer’s deterrence of showrooming. On the other hand, consumer showrooming as a mixed-channel shopping method makes the supplier less capable of adjusting the direct online demand according to its marginal cost of handling returns. Such a return-loss-propagation-moderating effect protects the downstream physical retailer from the upstream supplier’s strategic pricing that intends to shift sales from offline to direct online when the supplier finds it cost efficient to handle online product returns. Our study also shows that the retailer can replace the wholesale contract with the store-within-a-store model with a rental fee contract to leverage the upstream supplier’s incentive to mitigate the adverse effect of showrooming. The findings inform the physical retailer that the more critical issue may not be showrooming itself but aligning with the upstream supplier to promote offline sales in the presence of showrooming. This paper was accepted by Kartik Hosanagar, information systems. Funding: S. Kumar thanks Temple Center for International Business Education and Research for partially supporting this research. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2020.01990 .